EVALUASI IMPLEMENTASI MANAJEMEN RUMAH SAKIT DALAM RANGKA GREEN HOSPITAL DI WILAYAH BALI - Brando Harison Parlindungan Sigalingging (Program Studi Manajemen Lingkungan, 2019)
The increasing number of hospitals has an effect on the environmental damage of apabil not well managed. Environmental damage is a shared responsibility of both the government, the private sector and the public. In Indonesia today there is not even a hospital that already includes a green hospital, but the government prepares by 2020 every hospital is expected to participate in managing well by always considering the health, economic, ecological and social aspects so that the principle of fulfillment of the concept of sustainable development in the field health will be met, and hospitals can play an active role in minimizing the impacts of climate change. This research uses descriptive analysis techniques. From the results of this study states that of the 10 categories of world green hopsital hospitals in Bali still have much to prepare.